A comparison of the hallux valgus angle, range of motion, and patient satisfaction after use of dynamic and static orthoses. (December 2019) - Moulodi, Nasrin; Kamyab, Mojtaba; Farzadi, Maede
Highlights: Use of both static (night) and dynamic orthoses for 1 month can reduce the hallux valgus angle. To achieve better results, wear orthoses for longer time. The dynamic orthosis, increased the range of motion of first metatarsophalangeal joint. Dynamic orthosis appears to be an effective treatment for patients with mild and moderate hallux valgus. Abstract: Background: Conservative treatment is recommended for mild and moderate hallux valgus. The treatment may include two different types of orthoses: a dynamic orthosis and a static orthosis. The aim of this study was to compare the hallux valgus angle, hallux valgus range of motion, and patient satisfaction after the use of a dynamic and a static orthosis for the treatment of hallux valgus. Methods: Twenty-four participants contributed to this cross-over study. Participants were randomly allocated to orthotic treatments at the start. The hallux valgus angle and range of motion were measured using a goniometer. Pain, signs and symptoms, function in activities of daily living (ADL), function in sport and recreation, and foot and ankle-related quality of life (QOL) were measured using the Foot and Ankle Outcome Score (FAOS) questionnaire. The participants then switched to using the other orthosis. A one-way repeated measure ANOVA was conducted to compare the measured variables in subjects at 4 conditions before and after of using each orthosis. Results: There was a significant difference in the hallux valgus angle (p = 0.001). The Bonferroni test indicated that both static and dynamic orthoses significantly decrease the angle of hallux valgus, respectively before static, after static (mean difference = −2.67, p = 0.001) and before dynamic, after dynamic conditions (mean difference = −2.13, p = 0.02). There was also a significant difference in subjects range of motion by using a dynamic orthosis in before dynamic, after dynamic conditions (mean difference = 9.77, p = 0.01). There was no significant difference in total FAOS score within the conditions (p = 0.067). Conclusion: The use of both static and dynamic orthoses for 1 month can reduce the hallux valgus angle up to 2–3°. To achieve better results, it is suggested to wear orthoses for longer time. The dynamic orthosis also increases the passive range of motion of the first metatarsophalangeal joint and it seems to be effective during walking.